Development of iSpring Suite 11 Assisted RME Learning Media to Enhance Students’ Mathematical Critical Thinking Skills - Refi Dwi Mariska; Vepi Apiati; Depi Ardian Nugraha (Jurnal Pendidikan Matematika (JPM), 2025)
Students’ mathematical critical thinking skills remains low due to teacher-centered instruction, limited use of interactive digital media, and insufficient contextual learning experiences. Previous studies indicate that the Realistic Mathematics Education (RME) approach can support students’ reasoning, but its integration with interactive digital platforms such as iSpring Suite 11 has not been widely explored. This study addresses that gap by developing an RME-based interactive learning media assisted by iSpring Suite 11 for the topic of linear equations in two variables. The research used a Research and Development design with the ADDIE model. Data were collected through expert validation sheets, student response questionnaires, and a mathematical critical thinking skills test. Participants included media experts, material experts, instructional design experts, and 33 ninth-grade students at SMP Negeri 8 Tasikmalaya. Data analysis covered feasibility evaluation, practicality assessment, and effectiveness testing using the N-gain formula. The results show that the media was rated highly feasible by all experts, received very positive responses from students, and effectively improved mathematical critical thinking skills with an average N-gain score of 0.73, categorized as high. These findings demonstrate that iSpring Suite 11–assisted RME media provides meaningful learning experiences by combining contextual problem-solving with interactive digital features. The developed media can serve as an alternative digital tool to support mathematics instruction and strengthen students’ mathematical critical thinking skills.